(untitled) (Discourse of Law and Administration, 2026)
Civil society is portrayed as an important element of the state system. Due to its functioning, individuals have guarantees regarding the fulfillment of their own needs, as well as influencing the state. The implementation of activity by society does not exclude the obligation of public authorities to take action in various areas of public life, as well as activity in the sphere of people’s private lives. One of the main areas of activity that remains significant in the social and private sphere remains the problem of domestic violence. The aim of the work was to determine the legal role of civil society in taking action in the area of counteracting domestic violence. For this purpose, there was a necessity to determine the source of legitimacy of civil society and normative guarantees for taking action in this area.